1980
DOI: 10.1172/jci109651
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rabbit Hageman Factor by Homogenates of Cultured Rabbit Endothelial Cells

Abstract: A B S T R A C T Rabbit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…However, we reasoned that since sustained external balloon compression of the MCA may produce focal (e.g., ischemic) endothelial disruption, the coagulation cascade may be activated locally through both extrinsic (via tissue thromboplastin and Factor VII) and intrinsic (via Factor XII) pathways. 36 ' 37 In association with consequent prolonged complete stasis, as produced experimentally in the end-arterioles of the affected corpus striatum, sufficient thrombin may be generated to form occluding thrombus. In the absence of complete stasis, as in the MCA, thrombin generation would be insufficient for thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we reasoned that since sustained external balloon compression of the MCA may produce focal (e.g., ischemic) endothelial disruption, the coagulation cascade may be activated locally through both extrinsic (via tissue thromboplastin and Factor VII) and intrinsic (via Factor XII) pathways. 36 ' 37 In association with consequent prolonged complete stasis, as produced experimentally in the end-arterioles of the affected corpus striatum, sufficient thrombin may be generated to form occluding thrombus. In the absence of complete stasis, as in the MCA, thrombin generation would be insufficient for thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…HFa has recently been found to increase cutaneous vascular permeability in quantities as low as 3 ng, i.e., 1/10,000th the amount of HF present in 1 ml of plasma.2 In vitro studies of the system have demonstrated that negatively charged substances may activate the system. Vascular basement membrane (13) and collagen preparations (14,16), bacterial lipopolysaccharides (17), and serine protease(s) released from cultured endothelial cells (18), are capable of cleaving and activating the system. Thus through activation of complement, contact (HF), and clotting systems of plasma a number of effector agents are generated that could mediate many of the pathologic features of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of HF can be brought about by its exposure to negatively charged agents such as glass, kaolin (22), ellagic acid (33), a serine protease that is present in the microsomal fraction of endothelial cells (34), a combination of collagen and some other unidentified basement membrane components (27), and some but not all preparations of collagen (5)(6)(7)(8)(9)(10)(11)(12)(13). HF that has been activated during the "contact phase" of blood coagulation is inhibited by CI inactivator (35) and antithrombin III (36).…”
Section: Discussionmentioning
confidence: 99%